An overview of the special nexus between progressivist theorems and mainline christian Churches in Hungary - Zsolt, Csutak (Bogoslovni vestnik, 2024)
The so-called Christian conservative political turn and allegedly antiLGBTQ legislative measuresin governmental politicsin Hungary have affected the mainline Christian churches, as well. Critical Western progressive theoreticians and opinion leaders claim that the churchestend to legitimize and merely serve the objectives of politics, particularly in Hungary. The study analyzes the various clerical doctrines and statements concerning the new, progressive challenges, particularly the gender-related topics and the issue of church recognition blessing of same-sex marriage. It also demonstrates the biblical fundaments and doctrinal rigor that the mainline Christian churches in the West, and, especially in Hungary formulate and tend to base their dissenting stance in these highly controversial matters.
Keywords: Christianity; Hungary; krščanstvo; LGBTQ issues; Madžarska; progresivizem; progressivism; secularism; sekularizem; tradicionalizem; traditionalism; vprašanja LGBTQ